Data science for complex systems - Chakrabarti, Anindya S.; Bakar, K. Shuvo; Chakraborti, Anirban 1975- (Cambridge University Press, 2023)
This text provides an accessible guide to the tools and techniques of data science that can be utilised for the analysis of complex systems. This text is an invaluable resource for scientists, engineers and social scientists who require effective analysis of large quantities of data
Also issued in print: 2023. - Includes bibliographical references and index
Keywords: Data mining; Computational complexity; System theory / Data processing; Komplexes System; Data Science